2014
DOI: 10.1186/1471-2415-14-101
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein occlusion in retinal racemose hemangioma: a case report and literature review of ocular complications in this rare retinal vascular disorder

Abstract: BackgroudRetinal racemose hemangioma (RRH) is a rare congenital disorder that often co-occurs with other ocular complications. In this study, we present a case of RRH complicated with retinal vein obstruction in three branches and provide a review of ocular complications and associations with RRH.Case presentationOne case of RRH is presented. Fundus examination, fluorescein angiography (FFA) and optical coherence tomography (OCT) of the patient identified Group 3 RRH complicated with retinal vein occlusions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
1
28
0
2
Order By: Relevance
“…The cause for loss of vision is due to late ocular complications like retinal vein occlusion (45%), hemorrage (33%), macular edema or rare congenital vascular malformations like morning glory disc anomaly, Sturge-Weber syndrome and macroaneurysm. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause for loss of vision is due to late ocular complications like retinal vein occlusion (45%), hemorrage (33%), macular edema or rare congenital vascular malformations like morning glory disc anomaly, Sturge-Weber syndrome and macroaneurysm. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Congenital arteriovenous communications or retinal racemose hemangioma (RRH) is a rare, unilateral, non hereditary and sporadic phacomatosis characterized by the appearance of dilated and tortuous retinal vessels frequently extending from the optic disc to the retinal periphery. 1 Archer et al 2 have divided these AV communications into 3 groups depending on the size and location of vascular malformation. The first group is characterized by abnormal capillary plexus between the major vessels of the AV malformations and is usually asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…As in our patient, the large retinal AVMs in Wyburn-Mason syndrome usually cause cystic retinal degeneration [ 4 , 7 - 9 ]. Onder et al [ 10 ] reported a patient with Wyburn-Mason syndrome who developed serous retinal detachment and cystoid macular edema.…”
Section: Discussionmentioning
confidence: 76%
“…[ 4 ] This has been attributed to hyperdynamic flow through small caliber vessels and steal phenomenon caused by increased venous pressure and decreased arterial pressure. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed 167 cases of racemose angioma, among which only one case had MA. [ 5 ] There is a single case report by Tilanus et al . demonstrating fleeting MA in a case of racemose angioma over a course of 4 years.…”
Section: Discussionmentioning
confidence: 99%